Réponses

Meilleure réponse !
2014-04-26T17:12:36+02:00
Bonsoir

A)3(x-2)+2x = 3x - 6 +2x = 5x -6
B)-3(x+2)+5(x-3) = - 3x -6 +5x -15 = 2x -21
C)(-7+a)x(-4)+6(11-a)+5a = 28 -4a + 66 - 6a +5a = -5a +94
D)-2(4b-5)-(2+3b)+3(4b-1) = -8b +10 -2 -3b +12b - 3 = b +5

Si vous pourvues m aider ce serait super sympa! Merci d avance!


2014-04-26T17:16:28+02:00
A)
3(x-2)+2x=3x-6+2x
              =5x -6
B)
-3(x+2)+5(x-3)= -3x-6+5x-15
                     = 2x-21
C)
(-7+a)x(-4)+6(11-a)+5a= -7×(-4) -4a+66-6a+5a
                                 = 28+66-5a
                                 = -5a +94

D)
-2(4b-5)-(2+3b)+3(4b-1)=-8b+10-2-3b+12b-3
                                 = b +5

Si tu as besoin de plus d'explication n'hésite pas